Introducing Forensic Accounting Curiculum In Nigerian Universities: An Empirical Submission - Abiola, James O.; Adisa, Rilwan Ayinde (Archives of Business Research, 2020)
Forensic accounting is seen as one of the most important careers that will gain increased future demand, yet most Nigerian universities do not offer it as a separate course especially at undergraduate level. This paper therefore examined the perceived benefits and obstacles of integrating forensic accounting into the accounting curriculum of Nigerian universities. A survey research method was adopted using questionnaire prepared on a 5-point Likert scale and distributed among academics and students of tertiary institutions in Nigeria. The questionnaires were analysed using descriptive statistics. The findings revealed that the future demand and interest in forensic accounting education is expected to increase in spite of its attendant obstacles. It was also found that forensic accounting will promote responsible corporate governance, strengthen the credibility of financial reporting and make students more desirable in the market place. However, the major challenges of integrating forensic accounting into the accounting curriculum are the rigorous bureaucratic process in curriculum development for new programme and the lack of administrative interest and support. These results are useful to universities that are considering integrating forensic accounting into their accounting curriculum.